Hydrodynamics and dynamic capacity of cryogels produced with different monomer compositions - Chaves, Gabriel Luz; Gouveia Mol, Paula Chequer [UNESP]; Rodrigues Minim, Valeria Paula; Minim, Luis Antonio (Wiley-Blackwell, 2019)
Cryogels have received great attention in the area of bioseparation due to their characteristic of very large and interconnected pores. These materials allow rapid isolation of various biomolecules and permit that chromatographic processes are carried out at high flow rates. Nevertheless, studies regarding the effect of monomer concentration on the hydrodynamics and dynamic capacity of cryogels are scarce. In this study, supermacroporous polyacrylamide cryogels with different monomer and crosslinker concentrations were produced by cryopolymerization and activated with tris(hydroxymethyl)aminomethane. Porosity and permeability were determined and it was observed that these parameters changed with different monomer concentrations, indicating changes in the structure of the cryogels. Residence time distribution experiments were conducted at different flow rates and different mobile phase viscosities. As a function of composition of the cryogels, the axial dispersion increased and the flow pattern deviated considerably from the ideal plug flow model. For cryogels with lower crosslinker content, the effect of the mobile phase viscosity was more evident. The monomer composition changed the dispersion number and height equivalent to one theoretical plate, resulting in an impact on the adsorption capacity of the cryogel. Consequently, proper monomer and crosslinker concentrations may produce cryogels with suitable performance. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48507.
Keywords: adsorption; applications; functionalization of polymers; separation techniques